Penyelesaian Sengketa Pajak Penghasilan (PPH) Pasal 21 melalui Pengadilan Pajak - Ni Made Ina Sulastini; Ida Ayu Putu Widiati; I Nyoman Sutama (Warmadewa Press, 2021)
Taxes are an important element that assists the state in financing government activities in the development sector. The implementation of tax obligations is not uncommon for tax disputes to occur between taxpayers and authorized officials. This study aims to explain the authority of the tax court in resolving tax disputes and to analyze the process of settling income tax disputes article 21 through the tax court. The research used is normative legal research with a statutory approach, namely examining legal principles and case studies or legal literature. The data used are primary and secondary legal data sources. The results show that the authority of the Tax Court is to resolve tax disputes. The Tax Court in the case of Appeal only examines and decides disputes over the objection decision, and in the case of a lawsuit the tax court has the right to examine and decide disputes over the implementation of tax collection. In addition to the duties and powers referred to in article 31, the Tax Court also oversees legal counsel who provides legal assistance to disputing parties in the Tax Court hearings. In the event of an Article 21 Income Tax Dispute, the settlement is carried out with legal remedies. Objection if the taxpayer is not satisfied with the objection decision, the taxpayer can file an appeal to the Tax Court and the taxpayer can also file a lawsuit